2015
DOI: 10.1007/s00520-015-2747-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of severe depressive symptoms increases as death approaches and is associated with disease burden, tangible social support, and high self-perceived burden to others

Abstract: Prevalence of severe depressive symptoms increased as death approached and was associated with several modifiable factors. Healthcare professionals should become familiar with these factors to identify vulnerable patients. To decrease the likelihood of terminally ill cancer patients' severe depressive symptoms, they should receive effective interventions to manage their symptoms, appropriately foster social support to restore their fragile self-esteem due to depending on others, and lighten their SPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 44 publications
(76 reference statements)
1
26
1
1
Order By: Relevance
“…Furthermore, advanced cancer patients reporting high SPB suffered from greater physical symptom distress and psychological symptoms, whereas their family caregivers reported significantly more caregiving burden than caregivers of patients in the low‐burden group . The psychometric properties of the SPBS‐10 have not been formally tested in Taiwan, but its scores were negatively associated with QOL levels and positively associated with the likelihood of severe depressive symptoms in terminally ill Taiwanese cancer patients. In contrast, SPBS‐10 scores were only slightly correlated with terminally ill patients' symptom distress and functional dependence scores ( r = 0.21 and 0.25, respectively) , indicating that the SPBS not merely measures patients' dependence on other's practical help but broadly evaluates psychological and existential concerns about receiving help from others.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, advanced cancer patients reporting high SPB suffered from greater physical symptom distress and psychological symptoms, whereas their family caregivers reported significantly more caregiving burden than caregivers of patients in the low‐burden group . The psychometric properties of the SPBS‐10 have not been formally tested in Taiwan, but its scores were negatively associated with QOL levels and positively associated with the likelihood of severe depressive symptoms in terminally ill Taiwanese cancer patients. In contrast, SPBS‐10 scores were only slightly correlated with terminally ill patients' symptom distress and functional dependence scores ( r = 0.21 and 0.25, respectively) , indicating that the SPBS not merely measures patients' dependence on other's practical help but broadly evaluates psychological and existential concerns about receiving help from others.…”
Section: Methodsmentioning
confidence: 99%
“…Total ESDS scores range from 10 to 51; higher scores reflect greater dependence on help for personal and social functioning (Cronbach's α = 0.92 in this study). Construct validities of the Chinese‐version SDS and ESDS were established by Chinese‐version SDS and ESDS scores being positively associated with depressive symptoms and negatively associated with QOL in terminally ill Taiwanese cancer patients over their dying process.…”
Section: Methodsmentioning
confidence: 99%
“…(38) Fatigue and confusion are associated with mild to moderate depressive symptoms and anxiety is very frequently associated with severe depressive symptoms. (39)…”
Section: Assessment and Management Of Non-pain Symptomsmentioning
confidence: 99%
“…Our previous studies have documented patient-related determinants of high SPB in terminally ill cancer patients (Tang et al, 2017) and associations of SPB with cancer patients' EOL care preferences (Tang et al, 2017), quality of life (QOL; Tang et al, 2014) and severe depressive symptoms (Tang et al, 2016) at EOL. However, by definition, SPB derives from receiving care from another person.…”
mentioning
confidence: 99%
“…Care recipients and caregivers influence each other. Indeed, caregivers' depressive symptoms (Drabe et al, 2015;Hodges, Humphris, & Macfarlane, 2005) and QOL (Chen, Chu, & Chen, 2004;Drabe et al, 2015) are associated with those of their care recipients with cancer, and in turn, terminally ill cancer patients' depressive symptoms and QOL were significantly associated with their SPB (Tang et al, 2014(Tang et al, , 2016. However, few studies have comprehensively investigated caregiver-related factors associated with patients' SPB (Gauthier et al, 2007;Kowal et al, 2012;McPherson, Wilson, Lobchuk, et al, 2007), with only weakto-moderate correlations reported between caregiving burden and high SPB.…”
mentioning
confidence: 99%